2015
DOI: 10.1097/aog.0000000000000857
|View full text |Cite
|
Sign up to set email alerts
|

Risks Associated With Smallpox Vaccination in Pregnancy

Abstract: Objective To estimate the maternal and fetal risks of smallpox vaccination during pregnancy. Data Sources MEDLINE, Web of Science, EMBASE, Global Health, ClinicalTrials.gov, and CINHAL from inception to September 2014. Methods of Study Selection We included published articles containing primary data regarding smallpox vaccination during pregnancy that reported maternal or fetal outcomes (spontaneous abortion, congenital defect, stillbirth, preterm birth, or fetal vaccinia). Tabulations, Integration, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 38 publications
0
19
0
5
Order By: Relevance
“…The primary infertility is defined as women who do not have experienced a pregnancy without using of contraception after 1 year of intercourse and secondary infertility refers to the inability of women for pregnancy after experience at least one pregnancy in the past [19]. Spontaneous abortion was considered as the ending of pregnancy before 20 weeks of gestation and stillbirth as death occurring after the 20th week of gestation [20]. Also, a newborn delivered before 37 weeks of gestation was considered as a preterm birth and a neonate delivered after 42 weeks of gestation was considered as a postterm labor [12].…”
Section: A-obstetrical Information Questionnairementioning
confidence: 99%
“…The primary infertility is defined as women who do not have experienced a pregnancy without using of contraception after 1 year of intercourse and secondary infertility refers to the inability of women for pregnancy after experience at least one pregnancy in the past [19]. Spontaneous abortion was considered as the ending of pregnancy before 20 weeks of gestation and stillbirth as death occurring after the 20th week of gestation [20]. Also, a newborn delivered before 37 weeks of gestation was considered as a preterm birth and a neonate delivered after 42 weeks of gestation was considered as a postterm labor [12].…”
Section: A-obstetrical Information Questionnairementioning
confidence: 99%
“…Gebelikte canlı aşısı kontrendike olduğundan, inaktif polisakkarid aşı (Tyiphim Vi) aşılama gerektiğinde uygulanabilmektedir [37].…”
Section: Tifo Aşısı (Typhim Vi) (Typhoid Vaccine (Typhim Vi)unclassified
“…However, there is some data available on stillbirth rates following immunization showing no safety concerns [84], [85], [86]. A meta-analysis of eleven studies reported data on stillbirth (defined as fetal death ≥20 weeks of gestation) and found that the smallpox vaccination is not associated with an increased risk of stillbirth, pooled RR 1.03 (95% CI: 0.75–1.40) [87]. A study conducted in Finland during a mass oral poliovirus immunization campaign conducted between 1984 and 1986 reported stillbirth rates among women who were pregnant during the period of vaccination and whose infants were delivered at the three major hospitals in the Helsinki area between 0.4% and 0.6%, depending on their trimester of exposure, compared with 0.45% in the reference cohort [88].…”
Section: Preamblementioning
confidence: 99%